Markov chain model of phytoplankton dynamics - Wieczorek, Radosław (Zielona Góra: Uniwersytet Zielonogórski)
A discrete-time stochastic spatial model of plankton dynamics is given. We focus on aggregative behaviour of plankton cells. Our aim is to show the convergence of a microscopic, stochastic model to a macroscopic one, given by an evolution equation. Some numerical simulations are also presented.
Keywords: phytoplankton dynamics; coagulation; fragmentation; Markov chain